Determining structure and action mechanism of LBF14 by molecular simulation. Issue 22 (12th December 2022) - Solbach, Florian; Bernardi, Austen; Bansal, Shivani; Budamagunta, Madhu S.; Krep, Lukas; Leonhard, Kai; Voss, John C.; Lam, Kit S.; Faller, Roland
Abstract: The recently discovered, membrane–active peptide LBF14 contains several non–proteinogenic amino acids and is able to transform vesicles into tubule networks. The exact membrane interaction mechanism and detailed secondary structure are yet to be determined. We performed molecular dynamics simulations of LBF14 and let it fold de novo into its ensemble of native secondary structures. Histidine protonation state effects on secondary structure were investigated. An MD simulation of the peptide with a lipid bilayer was performed. Simulation results were compared to circular dichroism and electron paramagnetic resonance data of previous studies. LBF14 contains a conserved helical section in an otherwise random structure. Helical stability is influenced by histidine protonation. The peptide localized to the polar layer of the membrane, consistent with experimental results. While the overall secondary structure is unaffected by membrane interaction, Ramachandran plot analysis yielded two distinct peptide conformations during membrane interaction. This conformational change was accompanied by residue repositioning within the membrane. LBF14 only affected the local order in the membrane, and had no measurable effect on pressure. The simulation results are consistent with the previously proposed membrane interaction mechanism of LBF14 and can additionally explain the local interaction mechanism. Communicated by Ramaswamy H. Sarma